Molecular phylogenetic analysis of spiny eels (Mastacembelidae: Mastacembelus) from the Rokel River basin and adjacent areas of Sierra Leone, West Africa - Kanu, Unisa Conteh; Zhang, E.; Jianzhong, Shen (Zootaxa, 2022)
Cytochrome b (Cytb) sequences from 23 specimens of Mastacembelus spp. from the Rokel River, Taia/Jong River basins, and Freetown Peninsula were used in this study. These sequences were used to perform a gene-based phylogenetic analysis along with closely allied congeneric species in the Upper Guinea Forest in Africa. The resulting phylogenies inferred from Cytb showed populations of M. liberiensis from the Rokel River basin clustered into an exclusive lineage being sister to the lineage formed by M. greshoffi from the Congo basin. The Freetown Peninsula population of M. liberiensis clustered with sequences previously identified as M. taiaensis from the Taia/Jong River basin, sister to sequences of M. taiaensis from the Rokel River basin. The paired lineages were sister to the lineage formed by sequences from samples of the Taia/Jong River basin. These findings lead to the following conclusions: (1) hidden species diversity of spiny eels exists in either the Rokel River or the Jong River basin; (2) a likely available name for this species from the Freetown Peninsula is M. laticauda distinct from M. liberiensis; (3) given the diversity within M. liberiensis observed in the rivers sampled in Sierra Leone, it seems likely that the remaining rivers of Liberia and Sierra Leone reported having M. liberiensis may also harbor undescribed diversity. It is difficult to elevate some available junior synonyms based solely on a phylogeny inferred from Cytochrome b. We suggest that more samples from the entire range of M. liberiensis are needed and an integrated approach is required.